HIV rapid testing in community and outreach sites: results of a nationwide demonstration project in Italy - Scognamiglio, Paola; Chiaradia, Giacomina; Giovanetti, Marta; Albertini, Emidio; Camposeragna, Antonella; Farinella, Massimo; Lorenzetti, Daniela; Oldrini, Massimo; Rancilio, Laura; Caraglia, Anna; Maraglino, Francesco Paolo; Ippolito, Giuseppe; et al. (BMC Public Health, 2018)
Background Globally the access to HIV testing has greatly increased over the past 30 years. Nonetheless, a high proportion of people living with HIV remains undiagnosed, even in resource rich countries. To increase the proportion of people aware of their HIV serostatus and their access to medical care, several strategies have been proposed including HIV rapid test programs offered outside health facilities. The aim of this project was to evaluate the feasibility and efficacy of the HIV rapid testing offered in community and outreach settings in Italy. Methods We conducted a national demonstration project on HIV rapid tests offered in community and outreach settings, including nongovernmental organization (NGO) facilities, primary care services for migrants and low-threshold services or mobile units for drug users (DU services). HIV rapid test on oral fluid (OraQuick®; Orasure Technologies) was anonymously offered to eligible people who presented themselves at the selected sites. Those with reactive results were referred to a specialized outpatient unit for confirmatory testing and medical care. Results Over a period of six months a total of 2949 tests were performed and 45.2% of individuals tested had not been previously tested. Overall 0.9% (27/2949) of tested people had a preliminary positive test. In NGO facilities the positivity rate was 1%. All subjects who performed their confirmatory test were confirmed as positive. In services for migrants the positivity rate was 0.5 and 80% were referred to care (with 1 false positive test). In DU services we observed the highest positivity rate (1.4%) but the lowest linkage to care (67%), with 1 false positive test. Conclusion Our project showed that the offering of an HIV rapid testing program in community and outreach settings in Italy is feasible and that it may reach people who have never been tested before, while having a significant yield in terms of new HIV diagnoses as well.